NADPH oxidase 5 and renal disease. Issue 1 (January 2015) - Holterman, Chet E.; Thibodeau, Jean F.; Kennedy, Christopher R.J.
<x xml:space="preserve">Abstract</x> Purpose of review To highlight the latest novel developments in renal NADPH oxidase 5 (Nox5) biology, with an emphasis not only on diabetic nephropathy but also on many of the other renal disease contexts in which oxidative stress is implicated. Recent findings Nox-derived reactive oxygen species have been shown to contribute to a wide variety of renal diseases, particularly in the settings of chronic renal disease such as diabetic nephropathy. Although much emphasis has been placed on the role of NADPH oxidase 4 in this setting, a growing body of work continues to uncover the key roles for other Nox family members, not only in diabetic kidney disease, but also in a diverse array of renal pathological conditions. The most recently identified member of the Nox family, Nox5, has for the most part been overlooked in renal disease, partly owing to its absence from the rodent genome. New evidence suggests that Nox5 may be a contributing factor in glomerulopathies and altered tubular physiology. Furthermore, Nox5 appears to harbor a significant number of single-nucleotide polymorphisms that alter its enzymatic activity. Summary Given the unique structure and expression pattern of Nox5, it may prove to be an attractive therapeutic target in the treatment of renal disease.